The Relationship Between Chatbots & AI Solutions and Human Capital Readiness in The Industry 4.0 Era Towards Customer Experience Satisfaction: A Case Study of Customer Service Talents in Multinational Corporation - Soeradhyo, Satriyo Adhipranoyo; Achmad Fajar Hendarman (Jurnal Manajemen Bisnis, 2025)
Since entering the Indonesian market in 2017, Decathlon Indonesia—a subsidiary of the global sports equipment retailer from France—has faced challenges in enhancing customer satisfaction and engagement in the competitive sports retail industry. This study analyzes the impact of Chatbot and Artificial Intelligence (AI) adoption and human resource readiness in the Industry 4.0 era on customer experience satisfaction. Employing a mixed-methods approach that integrates surveys, focus group discussions, and literature studies, the research applies the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), complemented by Industrial HR Mapping 4.0: Gap and Index. Findings reveal that Chatbots and AI solutions significantly improve customer satisfaction, yet human resource readiness remains a barrier, particularly in unstructured knowledge sharing. These results underscore the need for an integrated knowledge management (KM) system. Accordingly, the study recommends the SECI (Socialization, Externalization, Combination, Internalization) model to enhance cross-functional collaboration and customer service. Theoretically, this research extends TAM and UTAUT within sports retail in developing countries. Practically, it provides strategic insights for Decathlon and similar firms to leverage digital technologies while strengthening HR capacity to deliver superior customer experiences.